New insights into the genetic mechanism of IQ in autism spectrum disorders - Wang, Harold Z.; Qin, Hai-De; Guo, Wei; Samuels, Jack; Shugart, Yin Y. (Frontiers in Genetics, 2013)
Autism spectrum disorders (ASD) comprise a number of underlying sub-types with various symptoms and presumably different genetic causes. One important difference between these sub-phenotypes is IQ. Some forms of ASD such as Asperger’s have relatively intact intelligence while the majority does not. In this study, we explored the role of genetic factors that might account for this difference. Using a case–control study based on IQ status in 1657 ASD probands, we analyzed both common and rare variants provided by the Autism Genome Project (AGP) consortium via dbGaP (database of Genotypes and Phenotypes). We identified a set of genes, among them HLA-DRB1 and KIAA0319L, which are strongly associated with IQ within a population of ASD patients.